Pengaruh Kualitas Produk, Citra Merek, Harga, dan Promosi terhadap Minat Beli Produk Second Brand - A.ang Wahyu Saputro; Zulfa Irawati (SAFE-Network, 2023)
This study aims to determine the effect of product quality, brand image, price and promotion on the purchase intention of Second Brand products among consumers in Surakarta. In recent years, many people have wanted to buy Second Brand products. This resulted in a change in sales volume for Second Brand products in Surakarta. This research is a quantitative research, involving 200 community respondents in Surakarta. The data in this study were collected by means of a questionnaire via a Google form using a Likert measurement scale. The data analysis technique of this study used multiple linear regression with the SPSS version 21 program. The results of this study indicate that product quality has a significant effect on purchase intention, brand image has a significant effect on purchase intention, price has a significant effect on purchase intention and promotion has a significant effect on purchase intention. The results of the F test calculations show that Product Quality, Brand Image, Price, and Promotion have a simultaneous effect on the intention to buy Second Brand Products in Surakarta.